Dissociating motor impairment from five-choice serial reaction time task performance in a mouse model of Angelman syndrome - Negrón-Moreno, Paola N.; Diep, David T.; Guoynes, Caleigh D.; Sidorov, Michael S. (Frontiers in Behavioral Neuroscience, 2022)
Angelman syndrome (AS) is a single-gene neurodevelopmental disorder associated with cognitive and motor impairment, seizures, lack of speech, and disrupted sleep. AS is caused by loss-of-function mutations in the UBE3A gene, and approaches to reinstate functional UBE3A are currently in clinical trials in children. Behavioral testing in a mouse model of AS (Ube3am-/p+) represents an important tool to assess the effectiveness of current and future treatments preclinically. Existing behavioral tests effectively model motor impairments, but not cognitive impairments, in Ube3am-/p+ mice. Here we tested the hypothesis that the 5-choice serial reaction time task (5CSRTT) can be used to assess cognitive behaviors in Ube3am-/p+ mice. Ube3am-/p+ mice had more omissions during 5CSRTT training than wild-type littermate controls, but also showed impaired motor function including open field hypoactivity and delays in eating pellet rewards. Motor impairments thus presented an important confound for interpreting this group difference in omissions. We report that despite hypoactivity during habituation, Ube3am-/p+ mice had normal response latencies to retrieve rewards during 5CSRTT training. We also accounted for delays in eating pellet rewards by assessing omissions solely on trials where eating delays would not impact results. Thus, the increase in omissions in Ube3am-/p+ mice is likely not caused by concurrent motor impairments. This work underscores the importance of considering how known motor impairments in Ube3am-/p+ mice may affect behavioral performance in other domains. Our results also provide guidance on how to design a 5CSRTT protocol that is best suited for future studies in Ube3a mutants.